Differentiation of Anatomic Entities in the Dog Stifle Joint Following S10B Plastination: Comparative Colorimetric and Radiological Investigations - Bakici Caner (Sciendo, 2019)
The knee joint is not only the most important and complex structure to present during anatomy lectures, but also a significant region for radiologists and orthopedicians. The objectives of this paper are: 1) to evaluate the efficacy of plastinated specimens by measuring colorimetric differentiation and 2) to compare the anatomical structures of the images obtained from computed tomography (CT) and silicone plastination cross-sections and perform three-dimensional (3D) reconstructed models of the specimens. A total of 16 knee joints selected from the 10% formalin fixed/dissected group (n=6), non-fixed/dissected group (n=6) and non-dissected whole knee joint group (n=4) were scanned by CT and plastinated by using the S10B silicone technique. The color changes of the structures were quantitatively determined with the colorimeter device. Plastinated whole knee joints were cut transversally with a band saw and compared with CT images. Finally, 3D reconstruction of the knee joints was performed from CT images with the 3D reconstruction program. There were statistically significant differences between the fixed and non-fixed groups in terms of color changes (p<0.001). The anatomical structures were identified and matched in the cross-sections of plastinates and corresponding CT images. It was observed that plastinated samples were elastic, durable and non-hazardous specimens to use in the veterinary orthopedics and anatomy courses and lectures. It has been found that fixation was useful for the final product morphology. It is thought that the 3D images obtained from this study will support comprehension of the relationships between the bones, muscles, and ligaments.